Chlamydia antibody testing helps in identifying females with possible tubal factor infertility - Swapnil Singh; Shilpa Bhandari; Pallavi Agarwal; Priya Chittawar; Ratna Thakur (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Introduction: Chlamydia is an important cause of sexually transmitted diseases leading to tubal factor infertility. Background: This study aims to define the role of chlamydial antibody detection in predicting presence, nature and type of tubal pathology in laparoscopy. Materials and Methods: A prospective study was conducted on 200 consecutive patients undergoing laparoscopy as a part of infertility work-up. Preoperatively, serological determination of Immunoglobulin G (IgG) specific antibodies against Chlamydia Trachomatis was done by Enzyme linked immunosorbant assay (ELISA). Findings of laparoscopy were evaluated against presence or absence of chlamydial antibodies in serum. Results: Out of 200 patients,10 patients tested positive for chlamydial antibody. Chlamydial antibody was found positive in 20% and 22.7% of patients with tubal pathology and peri-hepatic adhesions of patients, respectively. The sensitivity of chlamydial antibody for diagnosing tubal pathology was found to be 20%, while specificity was 100%. The positive chlamydial antibody test was not statistically associated with involvement of one or both tubes and site of tubal block. Conclusion: Chlamydia antibody test does not appear to be good screening test for tubal pathology especially in Indian subcontinent. In view of its high specificity, this test can be used to identify patients with higher chances of tubal pathology requiring operative intervention